2015
DOI: 10.1016/j.antiviral.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Global update on the susceptibility of human influenza viruses to neuraminidase inhibitors, 2013–2014

Abstract: Four World Health Organization (WHO) Collaborating Centres for Reference and Research on Influenza and one WHO Collaborating Centre for the Surveillance, Epidemiology and Control of Influenza (WHO CCs) tested 10,641 viruses collected by WHO-recognized National Influenza Centres between May 2013 and May 2014 to determine 50% inhibitory concentration (IC50) data for neuraminidase inhibitors (NAIs) oseltamivir, zanamivir, peramivir and laninamivir. In addition, neuraminidase (NA) sequence data, available from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
122
2
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(130 citation statements)
references
References 31 publications
5
122
2
1
Order By: Relevance
“…The effectiveness of neuraminidase inhibitors has been evaluated in several meta-analyses, but authors differed in their conclusions (Dobson et al, 2015;Jefferson et al, 2014;Muthuri et al, 2014). Furthermore, there is an increasing number of viral isolates resistant to neuraminidase inhibitors, and resistance can emerge during treatment (Cheng et al, 2012;Takashita et al, 2015;. Adamantanes are active against influenza A virus only, but are now rarely used because of resistance (Cheng et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of neuraminidase inhibitors has been evaluated in several meta-analyses, but authors differed in their conclusions (Dobson et al, 2015;Jefferson et al, 2014;Muthuri et al, 2014). Furthermore, there is an increasing number of viral isolates resistant to neuraminidase inhibitors, and resistance can emerge during treatment (Cheng et al, 2012;Takashita et al, 2015;. Adamantanes are active against influenza A virus only, but are now rarely used because of resistance (Cheng et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…1B) genes of A/Fukuoka/SDC1/2015 indicated that it originated in India during the outbreak. The Indian-origin A(H1N1)pdm09 and all Indian viruses analyzed in this study belong to genetic clade 6B that contains majority of the globally circulating influenza viruses (5,6). Three amino acids characteristic of the Indian viruses causing the worst outbreak, S84N in the HA protein, and V13I and I314M in the NA protein, were detected.…”
Section: Communicated By Masayuki Saijomentioning
confidence: 81%
“…However, community clusters of oseltamivir and peramivir cross-resistant viruses occurred in Australia in 2011, and in Japan in 2013-2014, respectively (10,11). Significant numbers of these resistant viruses were also detected in the United States and China during the 2013-2014 season (6,12,13). The resistant viruses possessed an H275Y substitution in the NA protein.…”
Section: Communicated By Masayuki Saijomentioning
confidence: 99%
“…L40P, V83A, and N146K substitutions in the NA were observed only with the PB1-wild type-6:2 virus following prolonged passaging. Mutant A(H1N1)pdm09 viruses with an amino acid substitution in NA at the Leu-40 or Val-83 residue were isolated in the 2013-2014 influenza season (31). There is currently no evidence that these substitutions exert specific functional effects.…”
Section: Resultsmentioning
confidence: 99%